Discursive Formation of Local Patriotism of the Past: Balance of Communicative and Textual Environment and Peculiarities of Impact - L. N. Rebrina (Научный диалог, 2019)
The article is devoted to the study of information, conceptual and emotional balance of the communicative and textual environment of regional media in the context of the construction of local patriotism of the past and the characteristics of the impact on the mass addressee (on the example of the Volgograd region media). The principle of balance is considered as an integral principle of environmental friendliness. Local patriotism is defined as the discursive relationship between the subject and the object of patriotism. An integrative approach is used, which provides an opportunity to analyze linguistic and non-linguistic phenomena, to attract achievements in different fields of knowledge. The completeness of the event content reflection, the types of facts, the text superstructure; the graduation of the truth at the level of propositional content or propositional installation, the reactualization accuracy, focus and means of displacement of communicative focus, the phenomenon of recurrently, types of headlines; estimative definition for hyperonyms to objects of reactualization (the past, history) and basic place names of the region; the ratio of positive and negative emotional semantic elements, types of emotional tonality are examined. It is shown that the characteristics of the balance of the communicative-textual environment determine the impact on the cognitive and emotional spheres of the addressee. The results indicate that the implemented control of information, perceptions and interpretations of the addressee, selective, irregular, mosaic, “substitutional,” “non-personal,” “distance” nature of the formation of pictures in the past of the region, “eventization” of memory, which helps simplification and stereotyping of generated images, reduction of internalization, complicates the initiation of emotional involvement and the valuable relationship.